Pendampingan Pemanfaatan Sampah Plastik dan Kertas Untuk Media Pembelajaran Inovatif Bagi Guru di SDN 5 Bae, Kudus - Fina Fakhriyah; Savitri Wanabuliandari; Sekar Dwi Ardianti (Universitas Mathla'ul Anwar Banten, 2016)
A teacher must have an ability to create innovative learning media so can increase understanding and motivation of learners . The purpose of this activities is to provide knowledge for teachers in SD 5 Bae about utilization of plastic and paper for innovative learning media. The target of this activities is to provide information and assistance to teachers in SD 5 Bae on the use of plastic and paper for innovative learning media. The method used in this activities is the interactive training and mentoring. The results of this activities is the teachers are able to design, create and practice innovative learning media from plastic and paper waste.